Production Performance of Joper Chickens Fed with BSF (Black Soldier Fly) Maggots Cultivated in Different Media - Aprisansoni, Amar; Wiryawan, I Ketut Gede; Maslami, Vebera; Erwan, Erwan; Indarsih, Budi (Jurnal Biologi Tropis, 2025)
The unstable price of animal feed is then carried out to find alternative feed. The purpose of this study was to evaluate the effect of giving maggots raised in different media on the production performance of Joper chickens. Maggots were raised with three different feed media. P1 25% blood, 50% bran, 25% market waste; P2 is the same as P1 24% market waste and 1% rice bran fried foods, and P3 is the same as P1 23% market waste and 2% fried food waste. Experiment Feeding 200 two week-old Joper chickens was done randomly in four treatments. P0 was given self-mixing feed, while P1, P2, and P3 were given additional feed 20% maggot flour in self-mixing feed maggot research results First. The results of the maggot research show that the best media for treatment P2 was BK 95.18%, ash 10.69%, KA 5.1%, LK 17.54%, SK 16.32% and PK 54.35%. The use of 20% maggots in Joper chicken feed has no significant effect on the production performance and percentage of Joper chicken carcasses, but there are tendency on the weight of P2 chicken carcass containing 1% fried waste. It is recommended to use 20% in the second research ration.